Sufiks 子 (-zi) dalam Bahasa Mandarin Modern: Kajian Morfosemantik - Arum, Wulan Sekar; Sobarna, Cece; Sutami, Agnetia Maria Cecilia Hermina (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2025)
The research aims to identify the word classes that can combine with the suffix, determine whether derivational processes occur in its word formation, and analyze the presence of semantic change. Data were obtained from the Chinese Trends 2023–Today corpus in Sketch Engine, collected between April 18 and April 30, 2025. A qualitative descriptive method was employed to analyze the data. The results of this study are, 1) the suffix 子 -zi can attach to noun and adverb, 2) 14 words containing the suffix 子 -zi undergo derivation, all of which belong to the noun class, 3) 23 words containing the suffix 子 -zi exhibit semantic change, and the rest do not exhibit semantic change. Additionally, the analysis identifies new semantic domains not reported in previous studies, comprising the categories of earth, natural substances, construction, time, analysis, representation, identity, and expression. Overall, the research findings show that the suffix 子 -zi functions not only as a words complement, but it also capable to objectify actions, objectify conditions, objectify numerals, objectify classifiers of objects, serve as diminutive marker, change the meaning of objects into a way of approaching something, change the meaning of a short time into an uncertain period of time, and change the meaning of neutral into the meaning of emphasizing/affirming.Keywords – Item and Arrangement, Modern Mandarin Language, Morphology, Semantics, Suffix 子 –zi.